Uncovering the molecular organization of unusual highly scattered 5S rDNA: The case of Chariesterus armatus (Heteroptera) - Bardella, Vanessa Bellini; Cabral-de-Mello, Diogo Cavalcanti (Elsevier, 2018)
One cluster of 5S rDNA per haploid genome is the most common pattern among Heteroptera. However, in Chariesterus armatus, highly scattered signals were noticed. We isolated and characterized the entire 5S rDNA unit of C. armatus aiming to a deeper knowledge of molecular organization of the 5S rDNA among Heteroptera and to understand possible causes and consequences of 5S rDNA chromosomal spreading. For a comparative analysis, we performed the same approach in Holymenia histrio with 5S rDNA restricted to one bivalent. Multiple 5S rDNA variants were observed in both species, though they were more variable in C. armatus, with some of variants corresponding to pseudogenes. These pseudogenes suggest birth-and-death mechanism, though homogenization was also observed (concerted evolution), indicating evolution through mixed model. Association between transposable elements and 5S rDNA was not observed, suggesting spreading of 5S rDNA through other mechanisms, like ectopic recombination. Scattered organization is a rare example for 5S rDNA, and such organization in C. armatus genome could have led to the high diversification of sequences favoring their pseudogenization.
Keywords: Birth-and-death; Concerted evolution; Coreidae; Fish; Multigene family